Isochoric pressure-temperature behavior of lactalbumin+water reactive mixtures under subcritical conditions - Rodríguez Ruiz, Andrea Carolina (2024)
This study examines the pressure-temperature (P-T) behavior of reactive mixtures composed of lactalbumin and water under subcritical and isochoric conditions. The impact of density on the P-T behavior was investigated for an initial lactalbumin composition of 5%, covering a density range of 0.7597 g/mL to 0.85620 g/mL. Additionally, the effect of varying lactalbumin concentrations, ranging from 3% to 15% (w/w), at a constant initial density of 0.831 g/mL, was also studied. Isochoric lines and density values of the reactive mixtures were compared to those of pure water under identical pressure and temperature conditions in all experiments. Furthermore, the total soluble solids (TSS) content was analyzed after each experiment, along with the thermal stability of amino acids subjected to prolonged reaction periods and high temperatures.